Review of Identity in The Gypsy by Weam Almadady - Obaidat, Adnan Mahmoud Suleiman (Journal of Arabic Language Sciences and Literature, 2023)
The Gypsy, by the Moroccan novelist Wiam Al-Madadi, highlights the identity crisis experienced by modern-day humans. Al-Madadi employed characters through which she aimed to reveal her inner thoughts. The gypsy, Mahtab, and her daughter Qamar were the two central characters in the novel, employed to express the writer’s thoughts best. Through these two characters, Al-Madadi has creatively conveyed her thoughts about the various individual and group conflicts in the East and West. She particularly reflected upon the Desert Storm in Iraq and the associated contradictory stands of rejection and approval of that war. Moreover, the writer portrayed the individuals’ relationships manifested in the religious, historical, humanitarian, and ethnic conflict with others. The novel revealed that murder, conspiracy, and injustice are not only practiced by Muslims and Easterners, as portrayed by the Western media but rather practiced by Westerners, often shown in their relationships within the same society or in their attitudes towards their different civilizations.
Keywords: The novel; identity references; The Gypsy; Wiam Al-Madadi